2012
DOI: 10.1177/109804821201600105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Advertising-Focused, Short-Term Study Abroad Programs on Students’ Worldviews

Abstract: Global employers in the advertising industry are increasingly interested in hiring students with intercultural communication skills and cultural experience. While the 5&1&/(%'"3'-"1AH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The majority of study abroad participants are from the fields of science, technology, engineering, and math; business and management; and social science (Institute of International Education, 2015). Traditionally, study abroad programs involved studying in another country for a semester or more; however, trends have shifted in favor of short-term study abroad programs due largely to cost-effectiveness as well as evidence from the literature that learning still occurs (Hachtmann, 2012; Perry et al, 2012). According to the Institute of International Education (2015), short-term study abroad programs, defined as lasting over the summer to 8 weeks or less, accounted for 62.1% of all programs in 2013/2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of study abroad participants are from the fields of science, technology, engineering, and math; business and management; and social science (Institute of International Education, 2015). Traditionally, study abroad programs involved studying in another country for a semester or more; however, trends have shifted in favor of short-term study abroad programs due largely to cost-effectiveness as well as evidence from the literature that learning still occurs (Hachtmann, 2012; Perry et al, 2012). According to the Institute of International Education (2015), short-term study abroad programs, defined as lasting over the summer to 8 weeks or less, accounted for 62.1% of all programs in 2013/2014.…”
Section: Introductionmentioning
confidence: 99%
“…To address these constraints, study abroad experiences have shifted towards short-term program designs (8 weeks or less; Hachtmann, 2012; Perry, Stoner, & Tarrant, 2012). As a result, recent research efforts have focused on the impact of short-term study abroad programs on students and their learning and comparing these outcomes to longer term study abroad experiences.…”
mentioning
confidence: 99%
“…According to Hachtmann (2012), the globalized world presents opportunities and challenges for students and requires global competency and intercultural communication skills. Several markers used for evaluating global competency in higher education include substantive knowledge, intercultural communication skills, openness, fluency in a different language, tolerance of ambiguity, awareness of issues facing the community, cross-cultural empathy, and knowledge of the in-group and the out-group (Donatelli, Yngve, Miller, & Ellis, 2005;Engleberg et al, 2017;Olsen & Kroeger, 2001).…”
Section: International Virtual Collaborationsmentioning
confidence: 99%
“…Research has documented a consolidation wave of advertising agencies into big global media groups (e.g., Publicis) that offer an array of services via collaboration of talent around the world (Springer, 2018). Further, evidence shows that prospective employers in advertising are especially drawn to hiring students who have international advertising skills and cultural awareness (Hachtmann, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with college students who had studied abroad suggest the transformation stems from students’ ability to immerse with local customs and people, communicate in a new language, and take time for cultural self-reflection (Clapp-Smith & Wernsing, 2014). Likewise, an analysis of the effects of an abbreviated advertising-focused study abroad experience found that it led students to display lower levels of ethnocentrism and increased inspiration to explore cultures in more depth (Hachtmann, 2012).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%